(untitled) (Scientific journal of the Fergana State University, 2024)
Euzophera bigella is considered the dominant species in pomegranate agrocenoses. Its life cycle includes distinct stages: adult moth, egg, larva, and pupation. All developmental stages, particularly the larvae at different ages, were studied, and measurements of morphometric characteristics were taken. Based on local conditions, the phenological calendar for the pomegranate borer was developed. Under the conditions of the Fergana Valley, the pomegranate borer can produce 4 generations in some years and 5 generations in others, while in Surkhandarya, it produces 5 generations.